Fundamental food microbiology - Ray, Bibek; Bhunia, Arun K.
"Preface to the Fifth Edition The golden era of food microbiology has begun. All three areas of food microbiology, beneficial, spoilage, and pathogenic microbiology, are expanding and progressing at an incredible pace; thus, it is difficult for one to stay abreast of new developments. A genuine attempt has been made to capture those developments in this new edition. Spoilage-causing microorganisms are a major concern. To feed the growing population in the world, microbial food spoilage must be reduced, and improved intervention technologies must be developed. To achieve that goal, it is necessary to understand the problems; that would help to develop effective control methods for different types of foods, especially using the hurdle concept. In the past decade, foodborne pathogens have broadened their association with varieties of foods that were unexpected, such as Salmonella in peanut butter, fish, and spices; Listeria monocytogenes in cantaloupe and celery; and a new strain of Shiga-toxin producing Escherichia coli (O104:H4) with sprouts. To have a greater understanding of pathogen association in preharvest plants and meat animals, the concerted efforts of plant biologists, animal scientists, soil chemists, environmental scientists, agriculture and biological engineers, social scientists, and microbiologists are needed to address food safety and quality issues"